HISTOPATHOLOGICAL PATTERNS OF LUNG CANCER ALONG WITH THE CLINICO-RADIOLOGICAL CORRELATION IN A TERTIARY CARE HOSPITAL IN PAKISTAN (The Research of Medical Science Review, 2025)
Background: Lung cancer, characterized by histological heterogeneity and significant clinico-radiological implications, remains the leading cause of cancer- related mortality worldwide. Objectives: The study was carried out to assess in lung cancer patients the histological patterns, radiological findings and biomarker expression. Methods: From March to September 2024, tertiary care hospitals in Rawalpindi undertook this cross-sectional study. Including 140 lung cancer patients in all, demographic, clinical, and histological data were gathered. Six biomarkers—TTF-1, UBE2C, MCM2, MCM6, FEN1, and TPX2—were immunohistochemically stained. Results: Patients' mean age was 62.4 ± 10.2 years; 58.6% of them were men. Among the patients, 69.3% smoked. The most often occurring histological subtype (35%), followed by papillary (21%) and solid patterns (18%), was acinar carcinoma. The most frequently observed radiological features were pleural effusion (19%) and mediastinal involvement (14%). TTF-1 (83.6%), MCM6 (77.1%), and MCM2 (73.6%), revealed high positive rates according to immunohistochemical investigation. Significant relationships between tumor proliferation and DNA repair were shown by biomarkers including FEN1 (65.7%) and UBE2C (72.1%). Conclusion: Acinar carcinoma was the most common histological subtype, with pleural effusion being the most frequently observed radiological feature. Especially TTF-1, high biomarker expression emphasizes its diagnostic and prognostic relevance in lung cancer. These results underlined the need of including molecular and histological data into customized therapy plans.